Pharmacokinetics of Dolutegravir, nucleoside analogues, and intracellular metabolites using plasma separation cards: A comparative analysis with traditional sampling methods in healthy volunteers - Beth Thompson; Laura J. Else; Laura Dickinson; Stacey Edick; Ashley Zyhowski; Ken Ho; Leslie Meyn; Sujan Dilly-Penchala; Victoria Shaw; Ian McGowan; Saye Khoo; Rhonda M. Brand (PLoS ONE, 2026)
Objectives Adherence to antiretroviral therapy is essential for achieving viral suppression. Plasma separation cards (HemaSep; HS-DBS) provide advantages for pharmacokinetic (PK) analysis and adherence monitoring, including simplified sample collection. This study compared the PK of dolutegravir (DTG), nucleoside reverse transcriptase inhibitors (NRTIs), and their intracellular metabolites in the dried plasma and cellular fractions of HS-DBS against the appropriate gold-standard matrices: liquid plasma for parent drugs and Whatman DBS (WM-DBS) for NRTI metabolites. Methods The APT-POCT-01 clinical trial (NCT04302896) is an open-label study assessing drug concentrations following cessation in healthy volunteers. Participants were randomized (1:1) to receive DTG/FTC/TAF or DTG/3TC/TDF for 15 days. Paired liquid plasma (L-pL), HS-DBS, and WM-DBS samples were collected on Day 15 and following treatment cessation (0–336 hours post-final dose). Results 29 individuals were included in the PK analysis (15-TDF/14-TAF). Tenofovir diphosphate (TFV-DP) was quantifiable up to 14 days post-cessation in HS-DBS (TAF/TDF) and WM-DBS (TDF) (HS-DBS t½ > 17 days, WM-DBS t½ = 15 days). 3TC-TP and FTC-TP were eliminated more rapidly. Nucleoside di/triphosphate concentrations were 3–7-fold higher, with prolonged half-lives (TFV-DP, FTC-TP), compared with WM-DBS. TFV-DP levels were ~12-fold higher with TDF compared to TAF. For NRTI and DTG, HS-plasma resulted in 1.8-fold higher exposures compared to L-pL. Measurable HS-DBS concentrations were correlated with L-pL and WM-DBS, with Bland-Altman analysis indicating agreement between methods. Conclusions This study provides important insights into the elimination kinetics of NRTI, their intracellular metabolites and DTG. Plasma separation cards are a promising alternative for adherence monitoring, enabling simultaneous quantification of parent and intracellular moieties from a single sample. Differences in TFV-DP levels between TDF and TAF regimens, and DBS sampling method, underscore the need for matrix and regimen-specific interpretation to validate adherence benchmarks.